Antibody‐mediated blockade of JMJD6 interaction with collagen I exerts antifibrotic and antimetastatic activities. Issue 12 (8th August 2017) - Miotti, Silvia; Gulino, Alessandro; Ferri, Renata; Parenza, Mariella; Chronowska, Agnieszka; Lecis, Daniele; Sangaletti, Sabina; Tagliabue, Elda; Tripodo, Claudio; Colombo, Mario P.
ABSTRACT: JMJD6 is known to localize in the nucleus, exerting histone arginine demethylase and lysyl hydroxylase activities. A novel localization of JMJD6 in the extracellular matrix, resulting from its secretion as a soluble protein, was unveiled by a new anti‐JMJD6 mAb called P4E11, which was developed to identify new targets in the stroma. Recombinant JMJD6 binds with collagen type I (Coll‐I), and distinct JMJD6 peptides interfere with collagen fibrillogenesis, collagen‐fibronectin interaction, and adhesion of human tumor cells to the collagen substrate. P4E11 and collagen binding to JMJD6 are mutually exclusive because the amino acid sequences of JMJD6 necessary for the interaction with Coll‐I are part of the conformational epitope recognized by P4E11. In mice injected with mouse 4T1 breast carcinoma cells, treatment with P4E11 reduced fibrosis at the primary tumor and prevented lung metastases. Reduction of fibrosis has also been documented in human breast and ovarian tumors (MDA‐MB‐231 and IGROV1, respectively) xenotransplanted into immunodeficient mice treated with P4E11. In summary, this study uncovers a new localization and function for JMJD6 that is most likely independent from its canonical enzymatic activities, and demonstrates that JMJD6 can functionally interact with Coll‐I. P4E11 mAb, inhibiting JMJD6/Coll‐I interaction, represents a new opportunity to target fibrotic and tumor diseases.—Miotti, S., Gulino, A., Ferri, R., Parenza, M., Chronowska, A., Lecis, D., Sangaletti, S., Tagliabue, E., Tripodo, C., Colombo, M. P. Antibody‐mediated blockade of JMJD6 interaction with collagen I exerts antifibrotic and antimetastatic activities. FASEB J. 31, 5356–5370 (2017). www.fasebj.org